2022
DOI: 10.1302/0301-620x.104b4.bjj-2021-1227.r1
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the GAP II cage in the management of metastatic disease of the acetabulum

Abstract: Aims The aim of this study was to assess the clinical and radiological outcomes of an antiprotrusio acetabular cage (APC) when used in the surgical treatment of periacetabular bone metastases. Methods This retrospective cohort study using a prospectively collected database involved 56 patients who underwent acetabular reconstruction for periacetabular bone metastases or haematological malignancy using a single APC between January 2009 and 2020. The mean follow-up was 20 months (1 to 143). The primary outcome m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Table III shows some recent studies evaluating patients with metastatic bone disease [66][67][68][69][70][71][72][73][74][75][76] .…”
Section: Metastatic Bone Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table III shows some recent studies evaluating patients with metastatic bone disease [66][67][68][69][70][71][72][73][74][75][76] .…”
Section: Metastatic Bone Tumorsmentioning
confidence: 99%
“…In patients with disease progression requiring arthroplasty, conversion was uncomplicated. For larger osseous defects, Kennedy et al reported on the survival of an antiprotrusio acetabular cage in patients with periacetabular bone metastases 72 . They demonstrated 100% acetabular component survival at the final follow-up and concluded that antiprotrusio cages are a viable option in patients with periacetabular metastatic bone disease.…”
Section: Metastatic Bone Tumorsmentioning
confidence: 99%
See 1 more Smart Citation